Caught in the Act : The Viewer as Performer - Drouin-Brisebois, Josée; Hill, Greg A.; Horne, Stephen; Ninacs, Anne-Marie; Exhibition. Caught in the Act : The Viewer as Performer. Ottawa. National Gallery of Canada Ottawa. 17.10.2008 - 15.02.2009. (Ottawa : National Gallery of Canada Ottawa, 2008)
Marman, Jennifer ; Borins, Daniel ; Johnson, Glen ; Baden, Mowry ; Sterbak, Jana ; Dean, Max ; D'Andrea, Raffaelo ; Belmore, Rebecca ; Monkman, Kent ; Farmer, Geoffrey ; BGL ; Guerrera, Massimo ; LaTourelle, Rodney
biog. p. 250-255, biog. auteurs p. 255
Engels
boek
Keywords: Canada -- KASK